Clima organizacional e gespública: um estudo em um órgão público da cidade de Manaus - Bomfim, Betty Anubia Azevedo (2008)
To present research treats of the organizational climate in a public Organ of the Judiciary Power of the city of Manaus. The interest for the proposed theme lives in the perception concerning the dizzy change in the world of the organizations, phenomenon that reached the public sphere. For an appropriate approach of the theme it is vital presentation of some linked topics to the theme, like this being, this work is composed by two chapters. The first chapter contemplates the concepts and theoretical approaches on organizational climate, besides the characterization of the place of the research. The second chapter treats of the methods and techniques used in the research, as well as the description of the population, instruments and procedures adopted for what intends the present study. The objective of this study was to analyze the organizational climate of a Public Organ of the Judiciary Power in Manaus / Am, starting from the comparison between the first and the second instance of the referred Organ. The main hypothesis that orientated the research was the one that difference exists among the organizational climate noticed by the servants of the 1st and 2nd instances in the researched Public organ. Starting from this work, he hopes to produce knowledge for the understanding of the operation of the organization in the public service.